Lactate Dehydrogenase Levels as A Marker of COVID-19 Severity - Uswatun Hasanah; Ani Kartini; Nursin Abd Kadir; Agus Alim Abdullah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Knowing the severity of COVID-19 is important during a pandemic. Measurement of Lactate Dehydrogenase (LDH) levels is a simple, quick, and widely available laboratory test in most health facilities. Lactate dehydrogenase levels change significantly in patients with tissue damage including COVID-19 disease. The purpose of this study was to analyze the LDH levels as a marker of the severity of COVID-19. The research method used was a cross-sectional approach using primary data from 70 suspected COVID-19 patients from June to July 2021 at Labuang Baji Hospital, Hasanuddin University Hospital, and Makassar City Hospital. Samples were grouped into mild, moderate, and severe COVID-19. The LDH levels at the time of hospital admission were measured using an Architect device. Chi-Square, Kruskal-Wallis, and ROC curve statistical tests were used to obtain the LDH value with a significant value of p<0.05. The sample consisted of 24 mild COVID-19, 23 moderate COVID-19, and 23 severe COVID-19. The LDH levels in mild COVID-19 were 101.00 U/L (74.00-156.00 U/L) significantly different from moderate COVID-19 was 143.00 U/L (126.00-253.00 U/L) and COVID-19 were 291.00 U/L (177.00-655.00 U/L) (p<0.001) and had a very strong positive correlation (r=0.914). The ROC curve showed that LDH had a sensitivity of 91.3%, specificity of 94.7% with the cut-off >250.5 U/L, NPV of 96.4%, PPV of 87.5%, and accuracy of 91.3%. LDH levels increase along with the increasing severity of COVID-19 caused by tissue damage due to increased inflammatory response. LDH can be used as a marker of COVID-19 severity.